PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING DENGAN TEKNIK EXAMPLE NON EXAMPLE TERHADAP AKTIVITAS DAN HASIL BELAJAR KOGNITIF SISWA KELAS VIII SMPN 3 BATUKLIANG UTARA - Andriani, Lia; Samsuri, Taufik; Royani, Ida (Bioscientist : Jurnal Ilmiah Biologi, 2018)
The problem of implementing biology learning in class VIIIB SMPN 3 North Batukliang 2016/2017 school year is creative thinking skills and student cognitive learning outcomes are still not satisfactory, as evidenced by the existence of MID semester scores under the KKM (Minimum completeness criteria). Caused by the learning process not running effectively because of the use of ineffective learning models. The purpose of this study was to measure the effect of the Reciprocal Teaching learning model with the Example Non Example Technique on the cognitive activities and learning outcomes of students on the subject matter of the digestive system in humans class VIII SMPN 3 North Batukliang. The instrument used in this study was an observation sheet for student learning activities and tests for student cognitive learning outcomes. The results showed that there was an increase in student learning activities, for an average student learning activity in the control class of 2.9 which was included in the quite active category, while for the experimental class by 3.5 with the active category. The results of students' cognitive learning post-test obtained an average value in the experimental class of 85.8 and a control class of 80. The t-test analysis at the significance level of 5% was obtained tcount of 3.12 while the value of ttable with dk = 54 of 2, 05. This means that the value of t is greater than the table value (3.12> 2.05). Thus it can be concluded that there is an effect of the Reciprocal Teaching learning model with the Example Non Example Technique on the cognitive learning outcomes of students.